2009
DOI: 10.4269/ajtmh.2009.80.953
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Saccharomyces boulardii and Metronidazole Compared to Metronidazole Alone in Children with Acute Bloody Diarrhea Caused by Amebiasis: A Prospective, Randomized, Open Label Study

Abstract: The aim was to evaluate the efficacy of Saccharomyces boulardii (Sb) in addition to metronidazole in amebiasis. A prospective, randomized, open clinical trial was performed in 50 children presenting with acute bloody diarrhea caused by Entameba histolytica. Group A and B (each N = 25) was treated with metronidazole, but Sb (250 mg, twice daily) during the 7 days was added to Group B patients who were re-evaluated 2, 3, 5, 10, and 30 days after diagnosis. Duration of bloody diarrhea was significantly longer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…5 Also bloody diarrhea due to amebiasis in children is shortened in comparison to placebo when S. boulardii is added to metronidazole. 12 Yogurt is a coagulated fermented milk product that is the result of fermentation with L. bulgaricus and S. thermophilus and its fluid shelters these probiotic microorganisms. 5 The therapeutic dose of yogurt has been reported to be around 10 6 -10 9 CFU of Lactobacilli and Bifidobacteria .…”
Section: Discussionmentioning
confidence: 99%
“…5 Also bloody diarrhea due to amebiasis in children is shortened in comparison to placebo when S. boulardii is added to metronidazole. 12 Yogurt is a coagulated fermented milk product that is the result of fermentation with L. bulgaricus and S. thermophilus and its fluid shelters these probiotic microorganisms. 5 The therapeutic dose of yogurt has been reported to be around 10 6 -10 9 CFU of Lactobacilli and Bifidobacteria .…”
Section: Discussionmentioning
confidence: 99%
“…18,47,51 The overall quality was assessed and 4 studies were rated as "good" (low risk for bias), 43,45,48,50 13 studies rated as "fair," which were susceptible to some bias, 13,14,16,18,19,37,38,[40][41][42]44,49,51 and 5 studies rated as "poor" (high risk for bias). 17,39,46,47,52 Findings From Meta-analysis Seventeen studies (2102 participants) reported duration of diarrhea. 13,14,16,17,19,37,38,41,42,[44][45][46][47][48][49]51,52 The reduction in diarrhea duration ranged from 250.4 to 6.0 hours among included studies.…”
Section: Risk Of Bias Within Included Studiesmentioning
confidence: 99%
“…Briefly, only 1 study was adequate for all of the 4 methodological quality assessment parameters 43 and 1 was inadequate for all 4 parameters. 46 Eight studies were rated as adequate 14,16,19,37,43,45,48,51 and 4 were inadequate for generation of the allocation sequence, 17,39,46,47 and the method used for allocation sequence was unclear in 10 studies. 13,18,38,[40][41][42]44,49,50,52 Four studies were adequate, 14,43,45,48 14 studies were unclear, 13,16,18,19,37,38,[40][41][42]44,[49][50][51][52] and 4 studies were inadequate (as they used a method such as alternation.…”
Section: Risk Of Bias Within Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations